Characterizing the bacterial community across the gastrointestinal tract of goats: Composition and potential function - Lizhi Wang; Lei Jin; Bai Xue; Zhisheng Wang; Quanhui Peng (MicrobiologyOpen, 2019)
Abstract The composition and function of the microbial community in the gastrointestinal tract (GIT) have increasingly captured the attention of nutritionists because these traits affect the nutrient utilization efficiency and health of host animals. Little information has been reported on these aspects of the goat GIT. This study used 12 female goats (weighing 20.70 ± 1.60 kg and 10 months of age) to examine the composition and function of the microbiota in the rumen, abomasum, jejunum, cecum, and colon. Total genomic DNA was extracted from chyme samples from different sections of the GIT, and the hypervariable region of the 16S rRNA gene was amplified by PCR using bacterial universal primers. The amplicons were sequenced on an Illumina MiSeq platform, and the biological information was analyzed using QIIME software. A total of 857 genera that belonged to 39 phyla were observed across the goat GIT, with Bacteroidetes and Firmicutes dominating. Our results revealed significant differences in the composition, diversity, and species abundance of the bacterial communities in the different sections of the GIT. However, the compositions of the bacterial communities in adjacent GIT segments showed similarities in addition to differences. The study indicated that there were significant differences in microbial function among the GIT regions. In particular, the relative abundances of genes involved in energy metabolism, amino acid metabolism, nucleotide metabolism, and glycan metabolism were overrepresented in samples from the forestomach, and genes related to energy metabolism, amino acid metabolism, and glycan metabolism were mainly enriched in samples from the small intestine. Additionally, the relative abundances of bacteria at the phylum and genus levels were significantly correlated with these metabolic functions. In general, there were significant differences in composition and potential function among the bacterial communities in the goat GIT.